2018
DOI: 10.3390/ijms19020335
|View full text |Cite
|
Sign up to set email alerts
|

Lignins: Biosynthesis and Biological Functions in Plants

Abstract: Lignin is one of the main components of plant cell wall and it is a natural phenolic polymer with high molecular weight, complex composition and structure. Lignin biosynthesis extensively contributes to plant growth, tissue/organ development, lodging resistance and the responses to a variety of biotic and abiotic stresses. In the present review, we systematically introduce the biosynthesis of lignin and its regulation by genetic modification and summarize the main biological functions of lignin in plants and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
592
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 875 publications
(609 citation statements)
references
References 137 publications
(154 reference statements)
9
592
0
8
Order By: Relevance
“…GO analysis showed that these DEGs were involved in different biological processes (Figure 8c). The four most significantly enriched GO terms were related to responses to biotic and abiotic stimulus, oxidation-reduction process, and growth and development, among which four genes were involved in lignin biosynthesis, which has been proposed to play an important role in resistance to microbes (Liu, et al, 2018a). And genes related to root hair remodelling, such as GSTF14 (GLUTATHIONE S-TRANSFERASE), PER8 (PEROXIDASE 8), PRP1 (PROLINE-RICH PROTEIN 1), and Immunoblot analysis was performed using anti-GFP antibody, and cFBPase (cytosolic fructose-1,6-bisphosphatase) was used as a loading control.…”
Section: Global Analysis Of Arabidopsis Gene Expression During Earlmentioning
confidence: 99%
“…GO analysis showed that these DEGs were involved in different biological processes (Figure 8c). The four most significantly enriched GO terms were related to responses to biotic and abiotic stimulus, oxidation-reduction process, and growth and development, among which four genes were involved in lignin biosynthesis, which has been proposed to play an important role in resistance to microbes (Liu, et al, 2018a). And genes related to root hair remodelling, such as GSTF14 (GLUTATHIONE S-TRANSFERASE), PER8 (PEROXIDASE 8), PRP1 (PROLINE-RICH PROTEIN 1), and Immunoblot analysis was performed using anti-GFP antibody, and cFBPase (cytosolic fructose-1,6-bisphosphatase) was used as a loading control.…”
Section: Global Analysis Of Arabidopsis Gene Expression During Earlmentioning
confidence: 99%
“…This is the case of RALF (Rapid ALkalinization Factor), which has been shown to arrest root growth and development in tomato and Arabidopsis (30), and caffeoyl shikimate esterase (CSE), which is an enzyme central to the lignin biosynthetic pathway (31). It is well known that lignin biosynthesis contributes to plant growth, tissue and organ development, and response to a variety of biotic and abiotic stresses (32). Some other Oe9 unique genes were associated with seed dormancy and sugar signaling, DOG1 (33), and positive regulation of germination, PELPK1 (34) (See Additional file 2: Table S2).…”
Section: New Assembly Version Of the Reference Olive (Cultivar Farga)mentioning
confidence: 99%
“…In general, a significant reduction in lignin content represents low yields, lodgings, and long‐term survival reduction in some perennial species . On the other hand, the reduction of lignin biosynthesis, besides exerting negative effects on the growth, development, and lodging of the plant, can also reduce biotic and abiotic resistance and stresses, which could result in a serious threat in agricultural production . However, it is possible to reduce lignin in some populations without causing damage to their physical fitness .…”
Section: Sugarcane Genetic Engineering and Genes Rolementioning
confidence: 99%
“…41 On the other hand, the reduction of lignin biosynthesis, besides exerting negative effects on the growth, development, and lodging of the plant, can also reduce biotic and abiotic resistance and stresses, which could result in a serious threat in agricultural production. 42 However, it is possible to reduce lignin in some populations without causing damage to their physical fitness. 41 Genetic modifications can improve the varieties of sugarcane to obtain cultivars with high cellulose contents and less recalcitrance (low lignin content) to bioconversion, without affecting the development of the plant under controlled conditions.…”
Section: Sugarcane Genetic Engineering and Genes Rolementioning
confidence: 99%